Povidone Iodine 1 % and Normal Saline as a Gargling Solution to Prevent Oral Mucousitis - Nursalam Nursalam; Ertawati Ertawati; Putri Kristyaningsih (Universitas Airlangga, 2009)
Introduction: Oral mucositis could affect children’s health status. The purpose of this study was to identify the difference of effectiveness between gargling with povidone iodine 1% and normal saline solutions in 5-15 years old children who received chemotherapy.Method: This study used pre-experiment static group comparison design. There were 18 respondents who divided into 2 treatment groups and 1 control group. The independent variable was gargling use solutions of povidone iodine 1% and normal saline and the dependent variable was oral mucositis.The level of mucositis measured using multiple variable mucositis rating scales then analyzed by means of statistical test mann whitney u test with significance level of α≤0.05.Result: The result showed that there were no difference between gargling use solutions of povidone iodine 1% and normal saline (p=0.930). Thus normal saline as good as povidone iodine 1% to prevent oral mucositis. It can be concluded that there was no difference between the use of povidone iodine 1% and normal saline as mouthwash to prevent oral mucositis.Discussion: It is recommended that patient with chemotherapy should be gorgled with povidone iodine and normal saline.